Validation of Advanced Computer Codes for VVER Technology: LB-LOCA Transient in PSB-VVER Facility - A. Del Nevo; M. Adorni; F. D'Auria; O. I. Melikhov; I. V. Elkin; V. I. Schekoldin; M. O. Zakutaev; S. I. Zaitsev; M. Benčík (Science and Technology of Nuclear Installations)
The OECD/NEA PSB-VVER project provided unique and useful experimental data for code validation from PSB-VVER test facility. This facility represents the scaled-down layout of the Russian-designed pressurized water reactor, namely, VVER-1000. Five experiments were executed, dealing with loss of coolant scenarios (small, intermediate, and large break loss of coolant accidents), a primary-to-secondary leak, and a parametric study (natural circulation test) aimed at characterizing the VVER system at reduced mass inventory conditions. The comparative analysis, presented in the paper, regards the large break loss of coolant accident experiment. Four participants from three different institutions were involved in the benchmark and applied their own models and set up for four different thermal-hydraulic system codes. The benchmark demonstrated the performances of such codes in predicting phenomena relevant for safety on the basis of fixed criteria.